2006
DOI: 10.1111/j.1540-8191.2006.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Triangular Resection and Folding of Posterior Leaflet for Mitral Valve Repair

Abstract: The conventional treatment of mitral insufficiency, due to posterior leaflet prolapse, is quadrangular resection. This technique sacrifices a great amount of valve tissue resulting in leaflet stiffness and altered annular geometry. To avoid such problems we performed a small triangular leaflet resection sparing the second-order chordae, a folding plasty, implantation of artificial chordae, and annuloplasty. Fourteen patients underwent this procedure. No hospital death and no repair failure were observed. Echoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 4 publications
(3 reference statements)
0
10
0
2
Order By: Relevance
“…7,12 Our findings in nondistended leaflets also suggest improved valve function, in terms of leaflet coaptation and mobility, compared with quadrangular resection. Although the outcomes of triangular resection were better than those with quadrangular resection, a 2-mm reduction in coaptation length and a 2- to 3-mm posterior displacement of the leaflet coaptation was measured in comparison with the control group.…”
Section: Discussionmentioning
confidence: 52%
“…7,12 Our findings in nondistended leaflets also suggest improved valve function, in terms of leaflet coaptation and mobility, compared with quadrangular resection. Although the outcomes of triangular resection were better than those with quadrangular resection, a 2-mm reduction in coaptation length and a 2- to 3-mm posterior displacement of the leaflet coaptation was measured in comparison with the control group.…”
Section: Discussionmentioning
confidence: 52%
“…This criticism is only partially overwhelmed by a triangular resection. 8,19 A proper approach is addressed to limit as much the resection of redundant tissue from the PML to restore annular dimension and shape and eventually to replace lost structures (ie, chordae tendinae).…”
Section: Discussionmentioning
confidence: 99%
“…(b) In the case of a large prolapsing posterior mitral leaflet with excessive leaflet height, Points a and b will be brought down to a different point on the posterior mitral annulus with annular plication. After triangular resection, the posterior mitral leaflet folding technique, described by Da Col et al [16] and Suri et al [17] are pictured. (c) In the case of a prolapsing posterior mitral leaflet with a limited extent, the leading edge is folded down a little after a triangular resection of the middle posterior mitral leaflet is performed with an additional pair of neochordae inserted; technique by Da Col et al [16] (d) In the case of the tall remaining lateral and medial border after a triangular resection of the middle posterior mitral leaflet, the leading edge is folded down in half without neochordae insertion, resulting in the ventricularization of the atrial side of the leaflet; technique by Suri et al [17] Without leaflet resection and annular plication, the posterior mitral leaflet horizontally folding technique without the change of native coaptation line, as described by Calafiore et al [7] and Hashim et al [8] are shown.…”
Section: Discussionmentioning
confidence: 99%
“…2a, b). Da Col et al [16] and Suri et al [17] performed a modified technique which involved flipping the margin over (i.e., PML ventricularization) after minimal triangular resection was performed with additional neochordae insertion or annuloplasty ring to prevent stiff movement of PML resulting from the wide resection associated with annular plication (Figures 2c, d). …”
Section: Discussionmentioning
confidence: 99%